Production and chemical composition of Istria and Pag whey cheese - Neven Antunac; Silvija Hudik; Nataša Mikulec; Mirjana Maletić; Iva Horvat; Biljana Radeljević; Jasmina Havranek (Mljekarstvo)
Istria and Pag curd are specific products that are mostly consumed fresh made in coastal areas and on islands. Curd is a sort of soft cheese. Due to its structure, it is very healthy. It has a high nutritional value which is the result of a great amount of proteins that are easy to digest and have a high level of utilization. The aim of this study was to describe the technological process of production, to determine the chemical structure and to suggest the value of standardization on the basis of sensory evaluation. The total of 28 curd samples were physically and chemically analyzed according to standard and accredited scientific methods. Statistical data analysis was carried out by using the procedures of Microsoft Office Excel (2007). According to water content in cheese, Istria and Pag curd belongs to a group of soft cheeses. On average the water content in Istrian curd was 56.62 %, and in Pag curd was 63.03 %. Istrian curd showed higher values of the fat content (28.9 %) and the fat in a dry matter (64.47 %) than Pag curd (23.25 % and 59.65 %). The sensory quality of Istrian curd was not as homogenous as of Pag curd. Based on the research results, it can be concluded that the physical and chemical structure of Istria and Pag curd was uneven, which is understandable if the production terms and conditions and the way of draining the curd are taken into account. The description of technological process of production and the understanding of physical and chemical structure of the curd, represent the significant contribution to the research and knowledge of domestic dairy products, which certainly should not be neglected in our dairy industry. In any case, these products deserve the experts full attention.